Peningkatan Kemampuan Siswa Menemukan Unsur-Unsur Intrinsik Fabel Melalui Model Pembelajaran Kooperatif Dengan Teknik NHT Kelas VII MtsN 2 Agam - Lisnawati Lisnawati (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2023)
This research is based on the author's observations in prohibiting material about fables. This research method is classroom action research using descriptive methods. This class PTK is carried out in at least two cycles, one cycle of three times two hours of lessons. In each cycle an analysis is carried out to see the successes and weaknesses of the classroom actions that have been implemented. The results can be used as material for consideration for the implementation of the next cycle. The research subjects were students of class VII. MTs Negeri 2 Agam, Agam Regency for the 2021/2022 academic year, with a total of 28 people. This research was conducted at MTs Negeri 2 Agam, in class VII.2 to be precise. MTs located in the state of Kamang Hilir, Kec. Kamang magek Based on research findings and discussion, the following conclusions can be drawn. First, the NHT (Numbered heads Together) technique in learning fable texts is well applied in PBM. This can be seen in student activities during the PBM. These student activities consist of students' attention to various PBM activities. Thus, it has a positive impact on improving students' fable reading skills. Second, the NHT (Numbered heads Together) technique can improve students' positive attitudes and behavior in PBM and student achievement in reading and analyzing the intrinsic elements of short stories can build self-confidence. Third, the NHT (Numbered heads Together) technique can improve fable analysis abilities. This increase can be seen in the average value of the first cycle is 47.6676% and the average value of the second cycle is 82.54%.